(untitled) (GUB Journal of Science and Engineering, 2024)
Over the past two decades, computer networks have been rapidly evolved to accommodate diverse users, hosts, services, and subnets with varying topologies. To evaluate the performance of these networks and their improvements, various methods have been employed and definitely, the Riverbed academic edition version 17.5 can be a better choice for that which can measure network performance by assessing the number of workstations, servers, hosts, services, subnets, and cable categories. In this article, Riverbed Academic Edition, Version 17.5 has been considered as a useful tool for the design and performance optimization of local area computer networks after completing rigorous simulation. The emergence of green computing has become vital as it is playing a crucial aspect of network design, with a focus on reducing power consumption and improving energy efficiency. Creating and duplicating scenarios is a common theme in green computing. At the same time, implementing network measurements can enhance bandwidth and overall performance in the local area. In the simulation, three scenarios - subnet, servers, and LAN connection – have been considered, with categorizations based on their complexity: simple, busy, and fast networks. By analyzing two network models in the evaluation methodology of the local area, the 4-building network model is determined to have superior performance than other models. To summarize, computer networks have been advanced significantly, though continuous improvements and developments are necessary to create efficient and dependable networks. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 9(1), 2022 P 71-81